2016
DOI: 10.4269/ajtmh.15-0070
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Guillain–Barré Syndrome in Aruba

Abstract: Abstract. The epidemiology of Guillain-Barré syndrome (GBS) in tropical areas is different compared with developed countries. We investigated the epidemiology of GBS on the Caribbean island of Aruba. Data were collected retrospectively from all 36 patients hospitalized with GBS between 2003 and 2011 in Aruba. We observed a seasonal distribution of GBS cases with a peak in February. The incidence rate (IR) fluctuated heavily between individual years. The overall IR was 3.93/100,000, which is higher than that ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
11
0
5
Order By: Relevance
“…In studies of children 15 years of age and younger, the highest male-to-female ratio was documented in El Salvador (1.8:1) [35] and the lowest in Brazil (1.2:1) [41] and Honduras 1.3:1 [37]. Among all ages, the highest male-to-female ratio was documented in Aruba (2.3:1) [46], followed by Argentina (1.6:1) [40], and the lowest in Brazil (1.3:1) [42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of children 15 years of age and younger, the highest male-to-female ratio was documented in El Salvador (1.8:1) [35] and the lowest in Brazil (1.2:1) [41] and Honduras 1.3:1 [37]. Among all ages, the highest male-to-female ratio was documented in Aruba (2.3:1) [46], followed by Argentina (1.6:1) [40], and the lowest in Brazil (1.3:1) [42].…”
Section: Resultsmentioning
confidence: 99%
“…The association of DENV infection with GBS is not well established. One multi-year study in Aruba found a positive correlation between number of GBS cases and laboratory-confirmed DENV infections (p = 0.004, Kendall’s tau-b) [46]. However, a study from Brazil reported no association between DENV outbreaks and GBS [64].…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed 135 full-text articles, of which 31 were eligible for inclusion ( Fig 1). Of the 31 studies, 28 reported countryspecific GBS rates from 13 LAC countries (Tables 1 & 2), 3 regional rates, [18,35,36] 15 background rates [18,[35][36][37][38][39][40][41][42][43][44][45][46][47][48], 11 rates during an arboviral outbreak [49][50][51][52][53][54][55][56][57][58][59], and 5 compared rates before and during an outbreak [27,[60][61][62][63]. Many studies presented data from Brazil (29%) and Colombia (16%), and the majority (68%) were published in 2015 or later.…”
Section: Resultsmentioning
confidence: 99%
“…In Veracruz, Mexico, 75% of GBS patients tested positive for C. jejuni infection in 2017 (after the peak of ZIKV) [49]. Studies in Aruba, Brazil, and Colombia-all except the one from Aruba were conducted during the ZIKV epidemic-found no association between C. jejuni infection and GBS [43,46,50,52,55,58]. A study in Brazil found respiratory infections to be present in 27% of GBS patients compared to 7% with gastrointestinal infections in pre-ZIKV years (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002) [43].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of ADEM and myelitis in Dengue are rare (6)(7)(8)(9). Guillain Barre syndrome (GBS) has been more commonly linked to dengue infection in a number of cases series associated with hypokalemic paralysis but also with demyelination (10,11). The neurologic syndromes associated with Dengue have also been reported in a case series from Jamaica (12); GBS was diagnosed in 3.7% but there were no cases of acute myelitis.…”
Section: Discussionmentioning
confidence: 99%